Characterization of women at risk of breast cancer - Rodolfo Javier Rivero-Morey; Leissay María Bordón-González; Jeisy Rivero-Morey; Vivian Lima-Navarro (Universidad Médica Pinareña, 2019)
Introduction: breast cancer is a serious health problem and one of the leading causes of death worldwide.